Microalga Euglena as a bioindicator for testing genotoxic potentials of organic pollutants in Taihu Lake, China - Li, Mei (Ecotoxicology (London, England), 2014)
The microalga Euglena was selected as a bioindicator for determining genotoxicity potencies of organic pollutants in Meiliang Bay of Taihu Lake, Jiangsu, China among seasons in 2008. Several methods, including the comet assay to determine breaks in DNA and quantification of antioxidant enzymes were applied to characterize genotoxic effects of organic extracts of water from Taihu Lake on the flagellated, microalga Euglena gracilis. Contents of photosynthetic pigments, including Chl a, Chl b and carotenoid pigments were inversely proportion to concentrations of organic extracts to which E. gracilis was exposed. Organic extracts of Taihu Lake water also affected activities of superoxide dismutase (SOD) and peroxidase (POD) of E. gracilis. There were no statistically significant differences in SOD activities among seasons except in June but significant differences in POD activities were observed among all seasons. The metrics of DNA fragmentation in the alkaline unwinding assay (Comet assay), olive tail moment (OTM) and tail moment (TM), used as measurement endpoints during the genotoxicity assay were both greater when E. gracilis was exposed to organic of water collected from Taihu Lake among four seasons. It is indicated that the comet assay was useful for determining effects of constituents of organic extracts of water on E. gracilis and this assay was effective as an early warning to organic pollutants